2008
DOI: 10.1038/ng.247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of rice plant architecture under domestication

Abstract: The closely related wild rice species Oryza rufipogon is considered the progenitor of cultivated rice (Oryza sativa). The transition from the characteristic plant architecture of wild rice to that of cultivated rice was one of the most important events in rice domestication; however, the molecular basis of this key domestication transition has not been elucidated. Here we show that the PROG1 gene controls aspects of wild-rice plant architecture, including tiller angle and number of tillers. The gene encodes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
286
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 394 publications
(312 citation statements)
references
References 26 publications
3
286
0
9
Order By: Relevance
“…Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 . However, the well-characterized domestication genes in rice were found to be fixed in both subspecies with the same alleles, thus supporting a single domestication origin [6][7][8][9]16 . Recently, a demographic analysis of single-nucleotide polymorphisms (SNPs) detected from 630 gene fragments suggested a single domestication origin of rice 17 .…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…Molecular phylogenetic analyses indicated that indica and japonica originated independently 3,10,20 . However, the well-characterized domestication genes in rice were found to be fixed in both subspecies with the same alleles, thus supporting a single domestication origin [6][7][8][9]16 . Recently, a demographic analysis of single-nucleotide polymorphisms (SNPs) detected from 630 gene fragments suggested a single domestication origin of rice 17 .…”
mentioning
confidence: 83%
“…We noticed that many loci with strong signals of selection were nearly identical in both indica and japonica where F ST between indica and japonica was extremely low, indicating that introduction of traits during domestication has in many cases involved introgression events. We noted that most well-characterized domestication genes, including Bh4 (hull colour 9 ), PROG1 (tiller angle 7,8 ), sh4 (seed shattering 5,6 ), qSW5 (grain width 35 ) and OsC1 (leaf sheath colour and apiculus colour 32 ), were among the 55 loci detected in the full population (Fig. 3).…”
Section: Screens and Annotation Of Domestication Locimentioning
confidence: 94%
See 2 more Smart Citations
“…Modification of plant architecture to create new elite cultivars is considered as a viable approach to increasing grain yield [1]. So far, numerous QTLs or genes controlling plant architecture have been cloned [2][3][4][5]. In the case of the 'Green Revolution', grain yields have been significantly increased by growing lodging-resistant semi-dwarf varieties of wheat and rice [6,7].…”
Section: Introductionmentioning
confidence: 99%